MISPRONUNCIATION OF ENGLISH FRICATIVES AND AFFRICATES PRODUCED BY ENGLISH STUDENTS OF STIKUBANK UNIVERSITY - Sigit Untoro; Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2020)
This article entitled “Mispronunciation of English Fricatives and Affricates Produced by English Students of Stikubank University.” This research aims to reveal the similarities and differences between English and Indonesian phonetic and to find out the fricatives and affricates categorized as difficult to be pronounced by the final semester students. The research focuses on phonetics, which is divided into two categories, fricative, and affricate. The researcher used the qualitative method in analyzing the data supported with some linguistics theory such as English Phonetic by Fromkin (1988), Indonesian phonetic by Chaer (2012), interference by Lado (1965), Saville (1971) Richards and Stenson (1978), Ellis (2006), and interlanguage by Ellis (1994)). The study revealed that there are six Indonesian fricatives that similar with the English fricatives, they are [f, s, z, ʃ, h, besides the different fricatives and affricates found on [v, θ, ð, ʒ, ʧ, ʤ]. The respondents failed in pronouncing labiodental fricatives [v] the deviation is 65% caused by devoicing mispronunciation, dental fricative [θ] with deviation 80% as the result of mispronunciation of two consonants which are in a close place of articulation, and palate-alveolar fricative [ʒ] is 68,3% as the result of spelling mispronunciation. Keywords: Phonology, phonetics, fricatives and affricates, interference, interlanguage.